KEDUDUKAN HAK ATAS AHLI WARIS ANAK KANDUNG NON MUSLIM DI INDONESIA DALAM PERSPEKTIF HUKUM ISLAM - Agus Purnomo (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTOne of the issues of inheritance which is still being debated is, heirs of different religions, both between Muslims (as heirs) and non-Muslims (as heirs) or vice versa. This is considering life in the present, especially as Indonesia as a heterogeneous nation (diverse) has increasingly developed and complex, where marriages of different religions or